Stereotip Gender dalam Film Anna Karenina - Perdana, Dionni Ditya (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Mass media had abig contribution to construct stereotypes of gender on society, one of them was through movies. The goal of this research was to seek how the gender stereotypes shown on a movie tittled AnnaKarenina. This research was a qualitative research which usingSemiotic analyses by Roland Barthes as the method. The result of this research indicated that this movie had many gender stereotype which represented bythe conversations and images to support the domestic area stereotype and ‘bad women’ labeling on society.